High stakes - Johansen, Iris (Grand Central Publishing, a division of Hachette Book Group, Inc., 2021)
"Logan Tanner lives the exhilarating life of a professional gambler, taking risks with nerves of steel. From casinos in Macau to Monte Carlo to Milan, he's racked up a fortune and become a living legend. But all the glitz and glamour hide a dark and violent past as an extractor -- a world that comes rushing back to him when the beautiful and innocent Lara Balkon enters his life. Soon Logan is drawn into the conflict between tow Russian mafia bosses over Lara, whose life now hangs in the balance. Logan has been offered something more valuable than money -- information he desperately needs -- in exchange for getting Lara out of Russia and to safety. Once together, Tanner discovers that Lara is a force to be reckoned with in her own right. Tanner's search for the truth leads them to the bright lights of Las Vegan, where the person who was hunting Lara now lies in wait for them. As the stakes climb with each deadly confrontation, Logan and Lara are catapulted into a game against pure evil. The odds are stacked against them, but it's a game they know they must play ... even if it may cost them their lives."-flyleaf.